An epidemiological study on ocular morbidities among school students in an urban area of South 24 Parganas, West Bengal - Mohanta, Munu; Dasgupta, Aparajita; Pan, Tania; Paul, Bobby; Bandyopadhyay, Lina; Mandal, Shamita (International Journal Of Community Medicine And Public Health, 2018)
Background: The estimated national prevalence of childhood blindness was 0.8 per 1000. Childhood blindness is a priority area because of the number of years of blindness in the life-time of a child. About one-third of India’s blind lose their eye-sight before the age of 20 years making early detection and treatment of ocular morbidity very crucial. This study aimed at estimating the proportion of ocular morbidities among school students in a secondary school in an urban area of West Bengal. Methods: It was a cross-sectional institution-based observational study conducted in August 2017 among 151 school students of 7th to 9th standard in an urban area of West Bengal. Data was obtained using a structured questionnaire followed by checking of visual acuity by Snellen’s chart. Visual acuity of 6/9 or more in any one eye was taken as a sign of visual impairment. Data was analysed using SPSS version 16.0. Results: Out of 151 students, 51.0% were found to have refractive error. The most frequently reported was difficulty in seeing among 43.7% of the students followed by headache while studying (36.4%) and pain in eyes (35.1%). Also, 9.9% of the students reported difficulty in seeing at night. Tests of association revealed that posture and screen time were significantly associated with presence of refractive error. Conclusions: The study revealed that high prevalence of refractive error among school students. Periodic screening of school children and spreading of awareness regarding correct posture and screen time are very essential to improve the quality of eye sight.